Prevalence of healthcare workers fully vaccinated against hepatitis B without circulating antibodies in Italy and role of age at baseline cycle vaccination: a systematic review and meta-analysis - Francesco Paolo Bianchi; Pasquale Stefanizzi; Giovanni Migliore; Andrea Martinelli; Luigi Vimercati; Cinzia Annatea Germinario; Silvio Tafuri (Expert Review of Vaccines, 2023)
Introduction Healthcare workers (HCWs) susceptible to hepatitis B represent an important public health concern. National and international guidelines recommend assessing the hepatitis B immune status of all HCWs and possibly vaccinating those found to be seronegative (non-responders). We conducted a meta-analysis to estimate the rate of hepatitis B sero-susceptibility among HCWs in Italy and to explore possible options for the management of non-responders. Areas Covered Nineteen studies, selected from scientific articles available in the Scopus, MEDLINE/PubMed and ISI Web of Knowledge databases between 1 January 2016 and 22 April 2022, were included. The prevalence of HBV-susceptible HCWs was 27.1% (95%CI = 23.2–31.7%). In a comparison by sex (males vs. females) the RR was 1.16 (95%CI = 1.03–1.31), and by full-cycle vaccination period (adolescence vs. infancy) the RR was 0.30 (95%CI = 0.25–0.37). Occupational health screenings for hepatitis B, with subsequent vaccination of non-responders, and exclusion of susceptible HCWs from high-risk settings have been common management strategies. Expert opinion It is highly probable that a proportion of the next generation of medical students and HCWs will not show circulating IgG on serologic evaluation. Therefore, more targeted efforts are needed to identify these individuals and actively immunize them.